Rapid sulfurization obscures carotenoid distributions in modern euxinic environments - Jian Ma; Xingqian Cui; Xiao-lei Liu; Stuart G. Wakeham; Roger E. Summons (Geochimica et Cosmochimica Acta, 2024)

Editorial: Current Topics in Marine Organic Biogeochemical Research - Stuart G. Wakeham; Cindy Lee; Carol Arnosti; Thorsten Dittmar; Kai-Uwe Hinrichs; Ann Pearson (Frontiers in Marine Science, 2020)

Analytical and Computational Advances, Opportunities, and Challenges in Marine Organic Biogeochemistry in an Era of “Omics” - Andrew D. Steen; Stephanie Kusch; Hussain A. Abdulla; Nevenka Cakić; Sarah Coffinet; Thorsten Dittmar; James M. Fulton; Valier Galy; Kai-Uwe Hinrichs; Anitra E. Ingalls; Boris P. Koch; Elizabeth Kujawinski; et al. (Frontiers in Marine Science, 2020)

Origin of Sedimentary BHPs Along a Mississippi River–Gulf of Mexico Export Transect: Insights From Spatial and Density Distributions - Stephanie Kusch; Julio Sepúlveda; Stuart G. Wakeham (Frontiers in Marine Science, 2019)

Stratification of archaeal membrane lipids in the ocean and implications for adaptation and chemotaxonomy of planktonic archaea - Chun Zhu; Stuart G. Wakeham; Felix J. Elling; Andreas Basse; Gesine Mollenhauer; Gerard J. M. Versteegh; Martin Könneke; Kai‐Uwe Hinrichs (Environmental Microbiology, 2016)
Summary Membrane lipids of marine planktonic archaea have provided unique insights into archaeal ecology and paleoceanography. However, past studies of archaeal lipids in suspended particulate matter (SPM) and sediments mainly focused on a small class of fully saturated glycerol dibiphytanyl glycerol tetraether (GDGT) homologues identified decades ago. The apparent low structural diversity of GDGTs is in strong contrast to the high diversity of metabolism and taxonomy among planktonic archaea. Furthermore, adaptation of archaeal lipids in the deep ocean remains poorly constrained. We report the archaeal lipidome in SPM from diverse oceanic regimes. We extend the known inventory of planktonic archaeal lipids to include numerous unsaturated archaeal ether lipids (uns‐AELs). We further reveal (i) different thermal regulations and polar headgroup compositions of membrane lipids between the epipelagic (≤ 100 m) and deep (>100 m) populations of archaea, (ii) stratification of unsaturated GDGTs with varying redox conditions, and (iii) enrichment of tetra‐unsaturated archaeol and fully saturated GDGTs in epipelagic and deep oxygenated waters, respectively. Such stratified lipid patterns are consistent with the typical distribution of archaeal phylotypes in marine environments. We, thus, provide an ecological context for GDGT‐based paleoclimatology and bring about the potential use of uns‐AELs as biomarkers for planktonic Euryarchaeota .

Biogenic polycyclic aromatic hydrocarbons in sediments of the San Joaquin River in California (USA), and current paradigms on their formation - Stuart G. Wakeham; Elizabeth A. Canuel (Environmental Science and Pollution Research, 2016)

Microbial biomass response to different quantities and sources of organic matter in B razilian coastal sediments - Cintia O. Quintana; Paula C. de Moraes; Marcos Y. Yoshinaga; Stuart G. Wakeham; Paulo Y. G. Sumida (Marine Ecology, 2015)
This study investigates the benthic microbial responses to organic matter ( OM ) variations in quantity and sources in two shallow water bays (Fortaleza and Ubatuba Bays) on the SE coast of Brazil on six occasions during the year. The pelagic and benthic compartments of the bays were evaluated by: (i) nutrients and chlorophyll a (Chl a ) in the water column; (ii) quantity and sources of OM in the sediment (Chl a , total organic carbon and total nitrogen and lipid biomarker composition); and (iii) microbial biomass in sediments as an indicator of active benthic response. Although there were changes in water‐column nutrients during the year, Chl a was fairly constant, suggesting a regular supply of microalgae‐derived OM to the sea bottom. Based on the composition of lipid biomarkers in sediments, OM sources were classified as mostly marine and with high contributions of labile (microalgae‐derived) OM . Labile OM composition varied from diatoms in the summer to phytoflagellates in the winter and tended to accumulate in areas protected by physical disturbances in one of the bays. Microbial biomass followed this trend and was 160% higher in protected than in exposed areas. This study suggests that the coupling between labile OM and benthic microbial biomass occurs primarily in protected areas, irrespective of the time of the year. Since meio‐ and macrofaunal assemblages depend upon secondary microbial production within the sediments, this coupling may have an important role for the benthic food‐web.

Influence of iron on fatty acid and sterol composition of marine phytoplankton and copepod consumers - Xi Chen; Stuart G. Wakeham; Nicholas S. Fisher (Limnology and Oceanography, 2011)
We conducted laboratory experiments to determine the influence of iron on the fatty acid (FA) and sterol composition of the diatom Thalassiosira oceanica , the cryptophyte Rhodomonas salina , the prymnesiophyte Isochrysis galbana , and the copepod Acartia tonsa that fed on these algae. Algal cells were cultured with no added Fe or with Fe added at 100 nmol L −1 . Fe‐deficient culture medium resulted in lower growth rates, cell volumes, and photosynthetic efficiencies for all algal species. The total mass of FA per cell was 2.2–3.1 times as high in Fe‐replete cells as in Fe‐deficient cells; on a carbon–normalized basis, the FA concentrations of Fe‐replete algal cells were 1.4–1.5 times as high. Differences were noted between Fe treatments for specific saturated, monounsaturated, and polyunsaturated FAs within each algal species. Total C‐normalized 20:5 ω 3 + 22:6 ω 3 concentrations declined 18%, 25%, and 35% in Fe‐deficient T. oceanica , R. salina , and I. galbana , respectively. Across all species, another consistent difference in FA composition between Fe treatments was for 18:4 ω 3, which had a C‐normalized concentration that was ∼ twofold higher in Fe‐replete algae. No consistent pattern for all algal species was evident for Fe effects on algal sterol concentration and composition, and in response to Fe limitation sterols were conserved more than C and FAs in these cells. Copepods feeding on Fe‐replete and Fe‐deficient algae displayed smaller differences in FA and sterol concentrations than in their algal diets. Differences in lipid concentration and composition between Fe‐replete and Fe‐deficient algae may partly explain the lower egg production rate of copepods fed Fe‐deficient algae.

Exchange between suspended and sinking particles in the northwest Mediterranean as inferred from the organic composition of in situ pump and sediment trap samples - Lynn Abramson; Cindy Lee; Zhanfei Liu; Stuart G. Wakeham; Jennifer Szlosek (Limnology and Oceanography, 2010)
The extent to which sinking particles disaggregate and exchange with surrounding material affects the efficiency of particulate organic carbon export to the deep sea. In 2003 and 2005, we compared the pigment and amino acid compositions of sediment trap and in situ pump samples collected in the northwest Mediterranean Sea to assess exchange between sinking and suspended particles. While sediment traps collected only sinking particles, in situ pumps collected both larger (> 70‐µm) particles, believed to represent the sinking fraction, as well as smaller (1–70‐µm) particles, believed to represent the suspended fraction. The organic compound compositions of sinking and suspended particles were very different and remained consistently so with depth, suggesting that exchange between them was limited. This difference was particularly pronounced during the high flux periods in spring. Sinking particles appeared to be composed of many fecal pellets and a few phytoplankton aggregates, and were enriched in diatom indicators. Suspended particles appeared to be more enriched in fresh phytoplankton and contained indicators of calcium carbonate‐bearing organisms. During the low‐flux summer period, the contribution of fecal pellet indicators to sinking particles was lower, whereas the contribution of microbial degradation products in both particle types was higher, possibly indicating greater exchange during periods of low flux when fecal pellets were not as abundant. Results from this study suggest that fecal pellets, although already degraded upon formation, are more robust than phytoplankton aggregates and, therefore, more likely to resist disaggregation and further decomposition during transit through the water column.

Detection of microbial biomass by intact polar membrane lipid analysis in the water column and surface sediments of the Black Sea - Florence Schubotz; Stuart G. Wakeham; Julius S. Lipp; Helen F. Fredricks; Kai‐Uwe Hinrichs (Environmental Microbiology, 2009)
Summary The stratified water column of the Black Sea produces a vertical succession of redox zones, stimulating microbial activity at the interfaces. Our study of intact polar membrane lipids (IPLs) in suspended particulate matter and sediments highlights their potential as biomarkers for assessing the taxonomic composition of live microbial biomass. Intact polar membrane lipids in oxic waters above the chemocline represent contributions of bacterial and eukaryotic photosynthetic algae, while anoxygenic phototrophic bacteria and sulfate‐reducing bacteria comprise a substantial amount of microbial biomass in deeper suboxic and anoxic layers. Intact polar membrane lipids such as betaine lipids and glycosidic ceramides suggest unspecified anaerobic bacteria in the anoxic zone. Distributions of polar head groups and core lipids show planktonic archaea below the oxic zone; methanotrophic archaea are only a minor fraction of archaeal biomass in the anoxic zone, contrasting previous observations based on the apolar derivatives of archaeal lipids. Sediments contain algal and bacterial IPLs from the water column, but transport to the sediment is selective; bacterial and archaeal IPLs are also produced within the sediments. Intact polar membrane lipid distributions in the Black Sea are stratified in accordance with geochemical profiles and provide information on vertical successions of major microbial groups contributing to suspended biomass. This study vastly extends our knowledge of the distribution of complex microbial lipids in the ocean.

Composition and degradation of marine particles with different settling velocities in the northwestern Mediterranean Sea - Madeleine Goutx; Stuart G. Wakeham; Cindy Lee; Marie Duflos; Catherine Guigue; Zhanfei Liu; Brivaëla Moriceau; Richard Sempére; Marc Tedetti; Jianhong Xue (Limnology and Oceanography, 2007)
Settling particles were collected from the Ligurian Sea in the northwestern Mediterranean Sea in May 2003 and separated by elutriation into different settling velocity classes (>230, 115–230, 58–115, and −1 ). Particles of the different classes were incubated for 5 d to study their biodegradability. Particulate opal content and organic compound composition (amino acids, pigments, lipids, and carbohydrates) were analyzed initially and at regular time intervals during the incubation period. Most particles (48–67% of total mass) sank at greater than 230 m d −1 and were dominated by large diatom‐derived aggregates produced during the spring bloom period. The initial organic composition and the biological lability of these particles varied with settling velocity. The strong phytoplankton signal was visible in all settling velocity classes, while slower settling particles carried with them a greater zooplankton and bacterial signature. As the different class particles decomposed, their compositions changed and became more similar with time, with a dominance of compounds that suggests a more degraded state: the amino acids χ‐aminobutyric acid and β‐alanine, the pigments pyropheophorbide and pheophytin, the deoxysugars fucose and rhamnose, and lipid metabolites (diglycerides and monoglycerides, alcohols, and free fatty acids). Biogenic opal in the particles dissolved faster in more degraded particles than in fresher particles, suggesting that loss of organic matter may expose opal to dissolution. The coupling of settling velocity and decomposition rate measurements shows quantitatively that slower settling particles are quickly degraded and faster settling particles retain their original biological signal to a greater degree. Greater preservation of faster settling particles testifies to the importance of these particles as food resources for bathypelagic and surface sediment communities.

Putative ammonia‐oxidizing Crenarchaeota in suboxic waters of the Black Sea: a basin‐wide ecological study using 16S ribosomal and functional genes and membrane lipids - Marco J. L. Coolen; Ben Abbas; Judith Van Bleijswijk; Ellen C. Hopmans; Marcel M. M. Kuypers; Stuart G. Wakeham; Jaap S. Sinninghe Damsté (Environmental Microbiology, 2007)
Summary Within the upper 400 m at western, central and eastern stations in the world's largest stratified basin, the Black Sea, we studied the qualitative and quantitative distribution of putative nitrifying Archaea based on their genetic markers (16S rDNA, amoA encoding for the alpha‐subunit of archaeal ammonia monooxygenase), and crenarchaeol, the specific glycerol diphytanyl glycerol tetraether of pelagic Crenarchaeota within the Group I.1a. Marine Crenarchaeota were the most abundant Archaea (up to 98% of the total archaeal 16S rDNA copies) in the suboxic layers with oxygen levels as low as 1 μM including layers where previously anammox bacteria were described. Different marine crenarchaeotal phylotypes (both 16S rDNA and amoA ) were found at the upper part of the suboxic zone as compared with the base of the suboxic zone and the upper 15–30 m of the anoxic waters with prevailing sulfide concentrations of up to 30 μM. Crenarchaeol concentrations were higher in the sulfidic chemocline as compared with the suboxic zone. These results indicate an abundance of putative nitrifying Archaea at very low oxygen levels within the Black Sea and might form an important source of nitrite for the anammox reaction.

The presence of ladderane lipids in the oxygen minimum zone of the Arabian Sea indicates nitrogen loss through anammox - Andrea Jaeschke; Ellen C. Hopmans; Stuart G. Wakeham; Stefan Schouten; Jaap S. Sinninghe Damsté (Limnology and Oceanography, 2007)
Distributions of ladderane lipids, which are characteristic of membranes of bacteria performing anaerobic ammonium oxidation (anammox), were determined in the northwestern Arabian Sea with respect to season, depth, and distance to the coast of Oman. Ladderane lipids were detected and quantified in suspended particulate matter (SPM) obtained from various water depths along a northwest‐to‐southeast transect during the spring intermonsoon period. Maximum concentrations of 5‐8 pg L −1 generally occurred at 500 m in the upper part of the oxygen minimum zone (OMZ). Fluxes of ladderane lipids obtained from sediment trap material sampled at 500‐m water depth ~350 km off the coast reveal a strong seasonal pattern apparently related to the annual monsoon cycle in the northern Arabian Sea, with highest fluxes of 125 ng m −2 d −1 observed during the southwest monsoon. This fourfold increase in flux during the SW monsoon compared to the spring intermonsoon period may indicate higher anammox bacterial productivity or enhanced export of ladderanes during a period of high particulate matter flux or both. Anammox, in addition to denitrification, seems to be responsible for a significant loss of nutrient nitrogen from OMZ waters in the Arabian Sea.

Isotopic compositions of lipid biomarker compounds in estuarine plants and surface sediments - Elizabeth A. Canuel; Katherine H. Freeman; Stuart G. Wakeham (Limnology and Oceanography, 1997)
We examined the isotopic compositions of fatty acids, sterols, and hydrocarbons isolated from three coastal macrophytes ( Zostera marina, Spartina alterniflora, and Juncus roemerianus ) in order to investigate the relative contribution of these vascular plants as sources of organic matter in coastal sediments such as Cape Lookout Bight, North Carolina. On average, lipid biomarker compounds extracted from the plants were depleted in 13 C by 3–5‰ relative to δ 13 C total organic carbon (TOC). However, individual compounds within each lipid class varied by up to 5.6‰. Trends in the isotopic compositions of lipids were consistent with δ 13 C TOC ; compounds obtained from Z. marina were the most enriched in 13 C and those from J. roemerianus were the most depleted. The range in isotopic abundances and molecular compositions of the sediments was greater than that obtained from the plants, indicating that additional, presently unidentified sources of organic matter contribute to the Cape Lookout Bight sediments. Similarity between the signatures for suspended particulate matter and the sediments indicates that much of the sedimentary organic matter is derived from algal and bacterial sources. Bacterial sources of organic matter are likely greater during summer/early fall, and incorporation of 13 C‐enriched bacterial biomass may contribute to observed seasonal shifts in δ 13 C TOC in the surficial sediments.